Peningkatan Kemampuan Fonologi Anak Usia Dini Melalui Kegiatan Bermain Berbasis Bahasa di TK YLPI Riau: Fonologis - Yuliawan, Tri; Shomary, Sudirman; Mukhlis, Muhammad; Roziah, Roziah; Hermaliza, Hermaliza; Kamarudin, Kamarudin; Wahyuni, Astri (UIR Press, 2025)
Phonological ability is a fundamental aspect of early childhood language development, closely linked to later literacy and communication skills. This study, titled